Bunga Bank (Riba) Dalam Pandangan Hukum Islam - Veri Mei Hafnizal (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2017)
In the modern economy, banks are intermediaries, and channeling of funds between the parties surplus with the underfunded. The purpose of writing this paper was to determine the bank interest under Islamic law. This research was conducted through a normative juridical research methods or research literature. The proposition which forbids the interest contained in the Qur'an Surat Ar-Rum verse 39, an-Nisa verse 160-161, Ali-Imran verse 130, al-Baqarah verse 275-279. Hadith of the Prophet one